2017
DOI: 10.1097/aog.0000000000001774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium, Vitamin D, and Hormone Therapy on Cardiovascular Disease Risk Factors in the Women's Health Initiative

Abstract: Objective To analyze the treatment effect of calcium + Vitamin D supplementation, hormone therapy, both, and neither on cardiovascular disease risk factors. Methods We conducted a prospective, randomized, double-blind, placebo controlled trial among Women's Health Initiative participants. The predefined primary outcome was low-density lipoprotein cholesterol (LDL-C). Results Between September 1993 to October 1998, a total of 68,132 women aged 50-79 were recruited and randomized to the WHI-Dietary Modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…The WHI results are similar to those reported by others (11)(12)(13). However, estrogen administered to postmenopausal women increases LDL clearance and lowers the levels of total cholesterol (TC), LDL-C, and apoliprotein B in plasma, showing the beneficial effects of estrogen in reducing the risk of cardiovascular disease (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 88%
“…The WHI results are similar to those reported by others (11)(12)(13). However, estrogen administered to postmenopausal women increases LDL clearance and lowers the levels of total cholesterol (TC), LDL-C, and apoliprotein B in plasma, showing the beneficial effects of estrogen in reducing the risk of cardiovascular disease (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 88%
“…Vitamin D3 is a fat-soluble vitamin that efficiently promotes the absorption and utilization of calcium elements in pregnant women, reduces the metabolism of calcium elements by the kidneys, and helps maintain the blood calcium level in the body [ 21 ]. Wang[ 22 ] et al stated that the detection of blood pressure levels in the maternal organism is effective in preventing the occurrence of hypertensive disorders [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that none of the RCTs were specifically conducted for evaluating the effect of supplemental vitamin D on lipids and lipoproteins. Interestingly, the largest trial (The WHI-Calcium+Vitamin D trial) conducted in 36,282 women showed that patients receiving combined vitamin D and omega-3 fatty acid supplementation had decreased serum very low-density lipoprotein cholesterol and serum triglycerides [42] while 400 IU vitamin D3 plus 1000 mg elemental calcium carbonate daily showed a decrease in LDL cholesterol after 6 weeks of intervention [43]. Consistently, our MR analysis in Chinese adults for the first time showed that each 25 nmol/l genetic increase in 25(OH)D concentration was associated with 0.058 mmol/L(0.22 mg/dL) and 0.034 mmol/L(0.13 mg/dL) lower total and LDL cholesterol, thus suggesting that 25(OH)D may play a causal role in lipid metabolism at least in Chinese adults.…”
Section: Discussionmentioning
confidence: 99%